Dampak Pembelajaran Berdiferensiasi terhadap Hasil Belajar Siswa Sekolah Dasar: (A Systematic Literature Review) - Nurul Husna Zakiyah; Irsyad Irsyad (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2026)
This study examined the impact of differentiated learning on the learning outcomes of elementary school students within the implementation of the Merdeka Curriculum. The Indonesian Programme for International Student Assessment (PISA) 2022 results indicated that, despite a rise in national ranking, Indonesian students' scores in literacy, numeracy, and science remained below the OECD average, raising concern about the effectiveness of student-centered learning strategies at the primary level. This article aimed to analyze and synthesize prior research findings regarding the implementation of differentiated learning and its impact on elementary school students' learning outcomes. A Systematic Literature Review (SLR) was conducted by searching Google Scholar, Garuda, ERIC, and Scopus databases using the keywords “differentiated learning,” “pembelajaran berdiferensiasi,” “elementary school,” and “sekolah dasar,” restricted to publications from 2021 to 2026. Fifteen relevant articles were thematically analyzed. The findings showed that differentiated learning, through content, process, and product differentiation, consistently improved cognitive learning outcomes, motivation, and active engagement of elementary students across subjects. Teacher readiness in diagnostic assessment was identified as a key supporting factor, while limited planning time remained the main obstacle. It was concluded that differentiated learning is a relevant strategy that should be strengthened in elementary classroom practice, supported by continuous teacher training.